2017
DOI: 10.18203/2394-6040.ijcmph20175163
|View full text |Cite
|
Sign up to set email alerts
|

Study of treatment outcome of tuberculosis among HIV co-infected patients: a cross sectional study in Aurangabad city, Maharashtra

Abstract: Background: Tuberculosis is the most common presenting illness among people living with HIV, including those who are taking anti-retroviral treatment. There were an estimated 1.2 million HIV positive new TB cases globally in 2014. Around 74% of these infected people live in sub-Saharan Africa. Aim and objectives were to study the treatment outcome of tuberculosis among HIV co-infected patients; to assess the outcome of TB treatment in TB patients with respect to their HIV status and to study the underlying fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 1 publication
(1 reference statement)
1
6
1
Order By: Relevance
“…In the current study, the death rate among the TB/HIV co-infected patients during TB treatment was 7.7%. Also, similar death rates were seen in study carried out in Mizan Aman (6%) [17], Aurangabad city, India (8.2%) [41], Addis Ababa, Ethiopia (8.3%) [26], South India (9%) [39], WHO African Region (9%) [23], Gondar (9.6%) [28], Viet Nam (10%) [36] and South Africa (10.5%) [24]. The death rate in our study was lower than the rate reported in deferent part of Ethiopia which reported a death rate ranging from 12.8 to 20.2% [16, 18, 31, 37, 42–44], Cameroon 29.4% [32], Karnataka India 15.7% [45], Yavatimal India 16% [38], Malaysia 21% [29], Ebonyi State Nigeria 19% [34], Free State province South Africa 17.4% [40], Iran 18.9% [33].…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…In the current study, the death rate among the TB/HIV co-infected patients during TB treatment was 7.7%. Also, similar death rates were seen in study carried out in Mizan Aman (6%) [17], Aurangabad city, India (8.2%) [41], Addis Ababa, Ethiopia (8.3%) [26], South India (9%) [39], WHO African Region (9%) [23], Gondar (9.6%) [28], Viet Nam (10%) [36] and South Africa (10.5%) [24]. The death rate in our study was lower than the rate reported in deferent part of Ethiopia which reported a death rate ranging from 12.8 to 20.2% [16, 18, 31, 37, 42–44], Cameroon 29.4% [32], Karnataka India 15.7% [45], Yavatimal India 16% [38], Malaysia 21% [29], Ebonyi State Nigeria 19% [34], Free State province South Africa 17.4% [40], Iran 18.9% [33].…”
Section: Discussionsupporting
confidence: 81%
“…The proportion of lost for follow up found in this study (1.7%) is comparable Mizan Aman 1.3% [17], Tigray 2% [16] and Gondar 2.2% [28] studies. This lost for follow up of TB/HIV co-infected patients is lower than many studies conducted in Ethiopia [18, 31], Africa [24, 32, 34, 40] and Asia [29, 35, 36, 39, 41]. The possible explanation might be a good implementation of the DOT program.…”
Section: Discussionmentioning
confidence: 80%
“…In this study, the magnitude of HIV was 24.5% which is similar to the finding of Harar town 22.8% [ 27 ], Felege Hiwot referral hospital (25%) [ 5 ], and Debre Tabor general hospital (24.2%) [ 48 ]. However, the prevalence was higher than previous studies at rural Ethiopian hospitals (1.7%) [ 22 ], Aurangabad city (7.28%) [ 26 ], and WHO 2019 TB report (8.6%) [ 7 ]. This high TB-HIV coinfection could be due to the higher proportion of patients from urban settings where there is a high prevalence of HIV.…”
Section: Discussioncontrasting
confidence: 56%
“…However, the rate of successful treatment outcome was higher than studies conducted by Biadglegne et al (26%) [ 5 ], Shargie and Lindtjørn (49.5%) [ 64 ], Tessema et al 29.5% [ 30 ], Rocha et al (77.1%) [ 22 ], Fiseha et al (28.9%) [ 14 ], Asebe et al (70.76%) [ 32 ], Ejeta et al (70.8%) [ 47 ], Kefale et al (30.32%) [ 15 ], Warkari et al (63.21%) [ 26 ], Adebimpe et al (78.7%) [ 23 ] and Ansa et al (64.0%) [ 65 ]. The satisfactory treatment success rate in our study might be due to improved adherence of TB patients associated with a good implementation of DOTs strategy, which was indicated by relatively lower failures and default rates.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation